Chapter 21 Differentiated integration in EU climate policy - Boasson, Elin Lerum (Taylor & Francis, 2022)
EU climate policy is characterized by significant degrees of differentiated integration. Although the two topics complement each other, differentiated integration and studies of EU climate policy have rarely been studied in conjunction. To address this gap, we develop a three-fold conceptualization that makes it possible to explore differentiation during the course of a policy cycle: policy output differentiation, policy outcome differentiation and policy impact differentiation. Our examination of two key elements of EU climate policy legislation-emissions trading and renewables policy-shows that differentiated integration is an uneven and multi-directional process that varies over time. We argue that differentiation is an important enabler for concerted action in EU climate policy and that differentiation at the policy output and outcome stages may facilitate greater harmonization at the impact stage. Differentiation at the impact and outcome level of the three (idealtype) policy stages does not automatically reflect differentiation at the output policy stage; it is rather that output differentiation may facilitate both high and low levels of differentiation at these later stages.